(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article provides a comprehensive exploration of the linguistic phenomenon of compounding, delving into its significance, types, and examples. It adeptly highlights the structural variations of compounds, distinguishing between endocentric and exocentric forms, offering a nuanced understanding of how words are formed through this process. The inclusion of examples from various linguistic contexts, such as German’s elaborate compound words, broadens the scope and illustrates the universality of compounding as a word-formation mechanism. The article effectively emphasizes the adaptability and productivity of compounding, particularly in response to technological advancements, showcasing its role in shaping contemporary language. A noteworthy aspect of the article is its recognition of compounding’s impact beyond linguistics. By linking the evolution of compound words to cultural shifts and societal changes, the article successfully positions compounding as a dynamic reflection of the zeitgeist. The discussion on linguistic economy and its role in professional and technical communication adds a practical dimension, underlining the utility of compounding in conveying complex ideas concisely. The supplementary information on creativity and literature expands the narrative, demonstrating how compounding serves as a tool for artistic expression. The article effectively weaves together linguistic, cultural, and creative dimensions, offering readers a holistic understanding of compounding and its multifaceted influence on language and human expression.